The Development of a resource guıde in assessıng students’ scıence manıpulatıve skılls at secondary schools - Fadzıl, Hidayah Mohd; Saat, Rohaida Mohd (Journal of Turkish Science Education, 2024)
Manipulative skills and abilities include skills in the handling and manipulation of materials and apparatus in the context of scientific investigation. Science teachers appeared to be struggling with the mode of assessment in making authentic evaluation of manipulative skills in laboratories. One of the contributing factors is due to the lack of instrument developed to assess these skills. This paper explains the development of a resource guide in assessing students‟ manipulative skills at secondary schools. This study employed a qualitative research methodology. The development of a resource guide in assessing students‟ manipulative skills involved three phases; (i) analysis, (ii) design and development, and (iii) implementation and evaluation. The evaluation of this guide was conducted qualitatively with 40 science teachers. Findings showed that the development of this resource guide is advantageous and beneficial to facilitate teachers in determining students‟ manipulative skills competency during practical work so that students can be more prepared for the implementation of the upcoming science practical examination. The findings may contribute towards enriching research on assessment of manipulative skills at the secondary school level. Science educators, either pre-service or in-service, may use this resource guide to improve their instruction during practical work.